2021
DOI: 10.1039/d1ra06728a
|View full text |Cite|
|
Sign up to set email alerts
|

Realization of multi-configurable logic gate behaviour on fluorescence switching signalling of naphthalene diimide congeners

Abstract: The implementation of functional congeners of naphthalene diimide experiencing fluorescence ON/OFF switching signalling in response to external stimuli, is suitably realized to construct multi-configurable molecular logic gates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Other studies have demonstrated chemosensors for binding metal ions, particularly with crown ethers at the bay positions [16][17][18][19]. A few examples of NDI-based logic gates are also known [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated chemosensors for binding metal ions, particularly with crown ethers at the bay positions [16][17][18][19]. A few examples of NDI-based logic gates are also known [20][21][22].…”
Section: Introductionmentioning
confidence: 99%